2016
DOI: 10.7326/m15-1839
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Erythropoietin-Stimulating Agents on Health-Related Quality of Life in Anemia of Chronic Kidney Disease

Abstract: KRESCENT and Manitoba Health Research Council Establishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 46 publications
3
47
0
3
Order By: Relevance
“…Although ESA administration is common practice in advanced CKD, the debate continues on target Hb and the effect on quality of life, which is likely higher for those with lower Hb levels. 363 Patients with advanced CKD (eGFR < 30 mL/min/1.73 m 2 ) should be managed in concert with nephrologists, especially when hemodialysis is contemplated. In those cases, as well as in some hemato-oncologic conditions, ESA therapy might be an option.…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%
“…Although ESA administration is common practice in advanced CKD, the debate continues on target Hb and the effect on quality of life, which is likely higher for those with lower Hb levels. 363 Patients with advanced CKD (eGFR < 30 mL/min/1.73 m 2 ) should be managed in concert with nephrologists, especially when hemodialysis is contemplated. In those cases, as well as in some hemato-oncologic conditions, ESA therapy might be an option.…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%
“…We considered the increasing number of missing values and dropouts as an important reason for bias and therefore determined point estimators with classification of missing values as MCAR and dropouts as MAR (see statistic section for details). Erythropoietin, which was administered to all study patients, does not seem to have a significant impact on QoL parameters according to a recent meta-analysis [50]. For a better reflection of age as an important predictor of death from a comorbid condition, the age-adjusted CCI was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a large, double-blind study of patients with NDD CKD, type 2 diabetes mellitus, and anemia showed only modest improvements in scores from the Functional Assessment of Cancer Therapy-Fatigue instrument, and no improved scores for the 36-Item Short-Form General Health Survey (SF-36) questionnaire, when patients received treatment for their anemia [46]. Additionally, a recent systematic review and meta-analysis concluded that there were no statistically or clinically significant differences between higher and lower Hb targets for HRQoL measured by SF-36 and Kidney Dialysis Questionnaire [47]. However, inherent to its focus on Hb target levels and specific HRQoL measures, potentially relevant studies were not considered due to the inability to combine results within a meta-analysis framework.…”
Section: Discussionmentioning
confidence: 99%